Engaging EFL Young Learners through Task-based Teaching with Character Education-enriched Materials - Iin Inawati; Didi Suherdi; Pupung Purnawarman (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2022)
This study aimed to investigate how the Task-Based Teaching Materials with Character Education Values (TBTMCEV) was implemented in teaching speaking in kindergarten context. The students’ speaking performance was also explored in this study. An exploratory case study research design was used in this study while the participants were two teachers and 14 students whose ages range between 5 and 6 years old. The data were gleaned from classroom observations, observation rating scale, and documents. The data analysis results that teaching speaking to kindergarten students in which Task-Based Teaching Materials with Character Education Values was implemented covers three stages including preparation, core activity and follow up as proposed by Cameron. The other result from data analysis shows that the students can produce three kinds of speaking performance during the teaching learning process, these include: naming objects, producing simple sentences, and getting involved in a dialog. The results lead to the conclusion that all of the students had chance to be actively involved in a dialog. It indicates that TBMCEV apparently could overcome resistance to the target language and create a need for speaking. Penelitian ini bertujuan untuk menyelidiki bagaimana Bahan Ajar Berbasis Tugas dengan Nilai Pendidikan Karakter (Task-Based Teaching Materials with Character Education Values/TBTMCEV)) diimplementasikan dalam pengajaran berbicara dalam konteks taman kanak-kanak. Kemampuan berbicara siswa juga dieksplorasi dalam penelitian ini. Desain penelitian studi kasus eksplorasi digunakan dalam penelitian ini dengan partisipan dua guru dan 14 siswa yang berusia antara 5 dan 6 tahun. Data diperoleh dari observasi kelas, skala penilaian observasi, dan dokumen. Hasil analisis data menunjukkan bahwa pembelajaran berbicara pada siswa taman kanak-kanak yang mengimplementasikan Materi Ajar Berbasis Tugas dengan Nilai Pendidikan Karakter meliputi tiga tahap yaitu persiapan, kegiatan inti dan tindak lanjut seperti yang dikemukakan oleh Cameron. Hasil lain dari analisis data menunjukkan bahwa siswa dapat menghasilkan tiga jenis kemampuan berbicara selama proses belajar mengajar, yaitu: menamai objek, memproduksi kalimat sederhana, dan terlibat dalam dialog. Hasil dari penelitian ini mengarah pada kesimpulan bahwa semua siswa memiliki kesempatan untuk terlibat aktif dalam dialog. Hal ini menunjukkan bahwa bahan ajar ini ternyata dapat mengatasi penolakan terhadap bahasa target dan menciptakan kebutuhan untuk berbicara.